PERAN ACCOUNT EXECUTIVE, CAMPAIGN STRATEGIST, & SALES PROMOTION MANAGER DALAM BRAND COMMUNICATION “BERCERITA DI BU LURAH” SEBAGAI UPAYA PENGUATAN BRAND IMAGE KOPI SUSU BU LURAH SEMARANG - Nadia Putri Mahendra; Yanuar Luqman (Interaksi Online, 2026)
This campaign is motivated by the high level of brand awareness of Kopi Susu Bu Lurah, which has not yet been followed by a strong brand image related to its core value of human connection. Consumer perceptions are still dominated by functional aspects, indicating the need for an integrated brand communication strategy. The “Bercerita di Bu Lurah” campaign was implemented through both online and offline approaches, utilizing Instagram and TikTok, as well as sales promotion activities such as “Ditraktir Bu Lurah” and event marketing programs like “Malam Puncak Pemilihan RT Terbaik” to encourage direct audience experience.The strategy aimed to strengthen the brand image as a space for social interaction, based on the concepts of Customer-Based Brand Equity (CBBE), Brand Communication, and Integrated Marketing Communication (IMC). The author served as Account Executive, Campaign Strategist, and Sales Promotion Manager in the development and implementation of the strategy.